PROTOTIPE SISTEM DIGITAL ARSIP INAKTIF PADA PKBM PAJA MANDIRI - Arief Herdiansah; Syepry Maulana Husain; Yani Sugiyani; Siti Fatimah Zamrotul Jannah; Alifah Alifah (Simposium Nasional Mulitidisiplin (SinaMu), 2020)
PKBM Paja Mandiri Tangerang is one of the non-formal educational institutions that provides SD (Package A), SLTP (Package B) and High School (Package C) equivalency education as well as various skills and other programs with +/- 1,875 students, quite a lot of archives the results of the teaching and learning process that must be managed. This research is applied research in order to assist PKBM Paja Mandiri in designing and developing a prototype digital archive management system. The data collection method was carried out by interviewing related parties at PKBM Paja Mandiri. After the data is obtained, the researcher conducts a needs analysis and designs a prototype digital archive system to be developed and implemented. The prototype of the Digital archive system produced and implemented in PKBM Paja Mandiri is felt to be very helpful for PKBM to manage documents more efficiently because of the use of information technology.